Optimized preparation of PPFAS and removal of heavy metals. Issue 1 (3rd October 2017) - Tang, Wenwei; Zhang, Mengtian; Wu, Wei; Zhang, Yazhou; Zeng, Xinping
Abstract : The basification method was used for the optimized preparation of a new flocculant, poly‐ferric aluminum phosphate sulfate (PPFAS). The Ferron method was used to analyze the distributions of the Fe and Al forms in PPFAS. The conditions of the optimized preparation of PPFAS were as follows: the n(OH)/n(Fe) ratio of 0.6, the n(P)/n(Fe) ratio of 1/5, and the reaction temperature of 60°C. After each addition of NaOH and Na3 PO4, the reaction was allowed to proceed for 10 min, and then, the reaction continued on the shaking table for 1 h; the aging process continued for 60 h at 25°C. Under these conditions, the content of the effective component, [Fe + Al]b, could reach up to 60%. The order of the removal rates of the mixed heavy metals by PPFAS is Cu(II)> Cr(III)> Pb(II)> Zn(II)> Cd(II). The order of the removal rates of the mixed complex heavy metals is EDTA‐Cd(II)> EDTA‐Zn(II)> EDTA‐Pb(II)> EDTA‐Cu(II)> EDTA‐Cr(III). © 2017 American Institute of Chemical Engineers Environ Prog, 37: 240–248, 2018